Environmentally Benign Synthetic Protocol for the Synthesis of Spiroquinazolinones Using Sustainable and Recyclable Choline Chloride Based Deep Eutectic Mixture - Kumar Tailor, Yogesh; Khandelwal, Sarita; Kumar Jain, Hemant; Kumar, Mahendra (Current Organic Synthesis, 2015)
Diversity oriented, efficient and environmentally benign synthetic protocol has been presented for the synthesis of spiroquinazolinones. The hybrid drug-like small molecules incorporating medicinally privileged heterocyclic systems have been synthesized by tandem reaction of 3-aminocrotonnitrile, phenyl hydrazine/ hydrazine hydrate, isatoic anhydride and isatin using deep eutectic solvent as efficient catalyst and environmentally benign reaction medium.
Keywords: HBD (Hydrogen bond donor)